Evaluation of Nasolabial Angle – A Cephalometric Study in Nepalese Adults with Normal Occlusion and Pleasing Facial Profile Visiting A Tertiary Level Hospital - Mahto, Ravi Kumar; Kafle, Dashrath; Rai, Diwas; Sakha, Rabina; Rajbhandari, Nikita (Orthodontic Journal of Nepal, 2022)
Introduction: Evaluation of nasolabial angle and its two associated components i.e. inclination of nose and upper lip is vital in orthodontic diagnosis and treatment planning. The normal value for these angular parameters has been found to vary in studies done previously in different populations. Aims and Objectives: The present study aimed to obtain normative value for nasolabial angle and its components as well as to study variation of these angular parameters in Nepalese adult male and female subjects with normal occlusion and pleasing facial profile. Materials and Method: Lateral cephalogram of 46 adult subjects (21 males and 25 females) with Class I occlusion and pleasing profile were selected from the archives of Department of orthodontics, Dhulikhel Hospital. Manual tracing and measurement of nasolabial angle (NLA) and 2 related parameters that affects nasolabial angle i.e., lower border of nose to Frankfort horizontal plane angle (N/FH), upper lip to Frankfort horizontal plane angle (L/FH) were done. Descriptive analysis was carried out and Student’s t-test was used to compare mean differences between the male and female subjects. Result: The mean values of NLA, N/FH and L/FH were 100.22 ± 10.36, 22.78 ± 7.46 and 79.46 ± 8.29 respectively. The mean value of NLA was 100.48 ± 10.07 in male subjects and 103.68 ± 10.57 in female subjects. Similarly, the mean value of N/FH was 21.90 ± 6.65 for males and 23.52 ± 8.14 for females. Also, the mean value of L/FH was found to be 78.62 ± 7.39 for males and 80.16 ± 9.07 for females. Conclusion: Normative value of nasolabial angle and its two associated parameters was established. Also, sexual dimorphism was observed with mean values of all the 3 parameters higher in female subjects as compared to male subjects.